(untitled) (Research, Society and Development, 2022)
This article deals with the preliminary injunction required in antecedent nature. It aims to analyze the circumstances in which the granting of such procedural request acquires stability in accordance with the legal rules currently in force. It is guided by the instrumental legal-dogmatic aspect, so it is a theoretical study based on Brazilian legislation, jurisprudence and doctrine. The deductive approach method is used; comparative, interpretive and analytical procedures; and the techniques of bibliographic and documental research. It discusses the legal regime of the provisional injunctions in the Code of Civil Procedure of 2015, revealing it as an instrument for reversing the burden of time in the process, in line with the constitutional guarantees regarding access to justice, substantial due process and reasonable duration of the process. It presents a special focus on the preliminary injunction required in antecedent nature, funneling the discussion to the institute of its stabilization, especially with regard to the legal presuppositions for this. Then, it addresses the conflict of positions of the chambers of the Superior Court of Justice about whether only the filing of an appeal in the strict sense would prevent stabilization or if other instruments of challenge would lend themselves to this, positioning in the sense that, based on the interpretation according to the Constitution, it must be understood that any instruments of challenge prevent stabilization. Finally, the autonomous action for challenge or confirmation preliminary injunction is exposed as a way to transmute stabilization into res judicata.